WOMEN AND PEACEBUILDING: CAN NIGERIA LEARN FROM OTHER COUNTRIES? Received: 18th March 2021; Revised: 27th April 2021, 19th June 2021; Accepted: 30th October 2021 - Akingbade, Retta E; Odebiyi, Adetanwa I (PEOPLE: International Journal of Social Sciences, 2021)
The inclusion of women in conflict resolution and peacebuilding is an important notion that has been well documented. Despite a widespread call for inclusive peacebuilding and progress in some African countries, in Nigeria, women are yet to achieve direct representation in formal peace and policy decision-making processes. The complex nature of conflict in Nigeria makes it imperative to explore all possible solutions to peacebuilding, including women’s potential, which remains largely untapped. This article examined, through a review of the literature, the strategies that women employed to achieve direct representation at the table in formal peace talks in Kenya and South Africa. The conflict situations in the two countries resonate to some extent, with some of the current insurgencies in Nigeria. The strategies of both the Kenyan and South African women were similar. High-profile women in the two countries brought their skillset and competencies to work across women’s groups regardless of social, religious, or political affiliation. They formed strong coalitions and were able to unite to the lobby, dialogue, and push for representation in formal peace talks. They engaged with the government to be included as negotiators and mediators. In Nigeria, there is a need to change patriarchal norms and traditional mindsets that prevent women from representation at the peace table through sensitization. It is also essential to enlighten relevant stakeholders, especially the government, on the importance of leveraging women’s skillset in peacebuilding initiatives.